Human Odometry with a Two-Legged Hopping Gait: A Test of the Gait Symmetry Theory. Issue 1 (2nd January 2020) - Harrison, Steven J.
Abstract: Biological odometry refers to the capacity for perceptually measuring distances traveled during locomotion. In the case of haptic odometry, information about distance traversed is generated from the movements of the legs, with coordinated leg motions (i.e., gait patterns) producing patterns of tissue deformation detectable by the haptic perceptual system. The gait symmetry theory of haptic odometry classifies gaits based upon the symmetry of muscle activation patterns. This classification identifies candidate higher-order variables of haptic odometry and provides a promising basis for understanding the associated patterns of tissue deformation detected by the haptic perceptual system. The theory successfully predicts biases (i.e., underestimations/overestimations) resulting from the manipulation of the gait patterns used in the outbound and return phases of homing tasks. We test gait symmetry theory by considering a previously unexamined key prediction. Two-legged hopping and walking have the same symmetry group classification, therefore, a homing task completed using any combination of two-legged hopping and walking as the outbound/return gaits should produce no systematic biases. Contrary to this prediction we observed systematic biases. We discuss the possibilities for modifying gait symmetry theory to account for our findings, and we present a new alternative theory based upon spatial reference frames.